2020
DOI: 10.1136/bmjopen-2019-035299
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapist-led mindfulness-based stress reduction for older adults living with subjective cognitive decline or mild cognitive impairment in primary care: a feasibility randomised control trial protocol

Abstract: IntroductionCommunity-dwelling older adults living with subjective cognitive decline or mild cognitive impairment may experience decreased efficiency in their overall functional performance. This decreased cognitive efficiency may result in anxiety, low mood, perceived stress and decreased emotional well-being and quality-of-life. These psychological symptoms may further exacerbate cognitive decline.Exploring non-pharmacological interventions such as mindfulness within primary care is vital in enabling individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The utilization of occupational therapists in primary care to address co-morbid physical and mental health conditions is an emerging area. This review found several studies that examined the impact of occupational therapy interventions in primary care settings and included quantitative mental health outcomes, however, these studies did not meet the eligibility criteria of including a comparison group (Cook and Howe, 2003; Guidetti et al, 2020; Stein and Miclescu, 2013; Tran et al, 2020). For example, one study described the impact of an OT-led mindfulness-based stress reduction program in a primary care setting and outlined a future randomized controlled trial (Tran et al, 2020).…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of occupational therapists in primary care to address co-morbid physical and mental health conditions is an emerging area. This review found several studies that examined the impact of occupational therapy interventions in primary care settings and included quantitative mental health outcomes, however, these studies did not meet the eligibility criteria of including a comparison group (Cook and Howe, 2003; Guidetti et al, 2020; Stein and Miclescu, 2013; Tran et al, 2020). For example, one study described the impact of an OT-led mindfulness-based stress reduction program in a primary care setting and outlined a future randomized controlled trial (Tran et al, 2020).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…This review found several studies that examined the impact of occupational therapy interventions in primary care settings and included quantitative mental health outcomes, however, these studies did not meet the eligibility criteria of including a comparison group (Cook and Howe, 2003;Guidetti et al, 2020;Stein and Miclescu, 2013;Tran et al, 2020). For example, one study described the impact of an OT-led mindfulness-based stress reduction program in a primary care setting and outlined a future randomized controlled trial (Tran et al, 2020). The future findings that will report on anxiety and depression outcomes will contribute to the evidence base in this field.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…The wait-list control group received the MBSR intervention post-three-months when the experimental group was completed. Our study protocol has been published previously [41]. All original study data, from focus group interviews to feasibility data such as attendance and field notes, were all kept under lock and key in a secure location within the clinic.…”
Section: Treatment Allocation and Randomizationmentioning
confidence: 99%
“…As previously described, feasibility outcomes included the following objectives: 1(a) patient recruitment, study retention, intervention adherence, and follow-up rates; and 1(b) acceptability of technology [41]. Data were collected from attendance records, home practice duration and completion, and computer tablet logins; attrition throughout the MBSR program was also tracked.…”
Section: Feasibility Outcome Measures and Acceptability Of Technologymentioning
confidence: 99%
“…A three-phase enriched environment protocol matching a multistage rehabilitation program applied post-head trauma or stroke, was found to improve cerebral blood flow, reducing cortical cellular loss (Zhan et al, 2020). Specific examples of implementation include encouraging end-user patients to identify new ways to deepen their experience of naturally occurring sound (Welch et al, 2022), incorporating mindfulness (Tran et al, 2020(Tran et al, , 2023 that may engage tinnitus core inhibitory systems and reduce stress. Multisensory novel stimuli, such as visual-auditory (experiencing unexpected or new sights and sounds) or motionauditory stimuli (such as singing and dancing), may activate similar limbic structures to narrow-band noise.…”
Section: End-user Patient-driven Experience Is Encouragedmentioning
confidence: 99%